2019
DOI: 10.1371/journal.pone.0213304
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and characteristics associated with positive QuantiFERON-TB Gold-Plus assay in children with confirmed tuberculosis

Abstract: Background Although QuantiFERON-TB Gold Plus (QFT-Plus), a new interferon-gamma release assay, has shown good performance in adults, little data is available in children. Methods De-identified data from TB-suspected patients age <18 years with QFT-Plus results, who were admitted or screened at the National Lung Hospital (NLH) in Ha Noi, Vietnam in 2017, were assessed. Logistic regression analyses were performed to determine the characteristics associated with having a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…This rate is much smaller than what has been reported from previous studies on QFT-IT (8, 18-21) but similar to the overall percentage of indeterminate results (4%) described in a recent metanalysis about IGRAs other than QFT-Plus (22). Importantly, Nguyen et al reported that only 2/222 children evaluated with QFT-Plus had indeterminate results, confirming our finding that QFT-Plus is also effective in children and can be a good alternative to TST (16). Among the 5 children with indeterminate results, 4/5 had comorbidities and only one child was otherwise healthy when screened for LTBI.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This rate is much smaller than what has been reported from previous studies on QFT-IT (8, 18-21) but similar to the overall percentage of indeterminate results (4%) described in a recent metanalysis about IGRAs other than QFT-Plus (22). Importantly, Nguyen et al reported that only 2/222 children evaluated with QFT-Plus had indeterminate results, confirming our finding that QFT-Plus is also effective in children and can be a good alternative to TST (16). Among the 5 children with indeterminate results, 4/5 had comorbidities and only one child was otherwise healthy when screened for LTBI.…”
Section: Discussionsupporting
confidence: 90%
“…The overall sensitivity of QFT-Plus for active TB was 83.3% and specificity was 90.1%. These rates are similar to what have been reported from previous studies on QFT-IT (8) but higher compared with rates of the only extensive pediatric study published so far on QFT-Plus that reported an overall sensitivity of 54.5% (16). Nevertheless, sensitivity raised to 84.2% when they exclusively evaluated pulmonary TB.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A recent longitudinal study in a high TB prevalence setting suggests that IGRAs are less sensitive than TSTs for the detection of LTBI [24]. The updated version of the QFT assay, QuantiFERON-TB Gold Plus, may perform better, but the available data in children currently remain limited [25], [26], [27].…”
Section: Introductionmentioning
confidence: 99%